Ecocardiografia como auxílio didático no estudo da morfologia, fisiologia e fisiopatologia do coração na hipertensão arterial - Segamarchi, Fábio Abdalla (2013)
Hypertension is a disease of high prevalence, oligosymptomatic, with low rates of blood pressure control and with serious consequences if not treated properly. The involvement of target organs can lead to serious restrictions in the quality of life on affected individuals, high financial costs to society and the public health system on Brazil (Sistema Único de Saúde). Echocardiography has an important role in risk stratification and clinical management of these patients. Moreover, the exam allows to visualize the structure and the functional characteristics of the heart, which can be an additional tool for teaching students and health professionals in training. The use of educational software in the medical field provides an interactive and autonomy learning. Objective: To use the images of echocardiography to develop software that will apply as a tool for the education of student health, allowing comprehend of normal cardiac structure and function and the heart compromised by hypertension. The secondary objective was to evaluate the software using qualitative and quantitative tools, including opinions and suggestions of students of medicine and nursing. Hypothesis: The use of the software can make teaching more attractive, agile and appropriate to communication technologies and contemporary education and allow the user to understand the real consequences of hypertension on the heart. Methodology: The software was developed from the author's own database of images using the author multimedia Flash® which allows the creation of animations and simulations in vector language, resulting in compact files that can be made available through the Web or on optical and magnetic media. The evaluation of the final product was made by students of medicine and nursing. Results: The software was well evaluated by students of medicine (n = 38) and nurses (n = 18) of the Faculdade de Ciências Médicas e da Saúde da PUC/SP, whose pre and post-tests of the material showed consistent growth of knowledge, either through self-assessment or objective open questions. Conclusion: The software using the echocardiography was effective in making easier the understanding of the impact caused by hypertension in the heart, in view of the complexity of educational content. The software can be useful to students, teachers and professionals in the health field